PRELIMINARY RESULTS OF INTERFEROMETRIC OBSERVATIONS OF THE QUIET SUN AT THE FREQUENCIES 8 – 32 MHZ - Shepelev, V. A.; Melnik, V. N.; Vashchishin, R. V. (Одеські астрономічні публікації, 2018)
We studied a radio emission of the quiet Sun at decameter wavelengths to determine its angular dimensions. Observations were conducted using interferometers composed of antenna sections of the UTR-2 radio telescope. A number of interferometers with baselines of 225 to 1400 m, oriented along the meridian, operated at two frequencies of 20 and 25 MHz with a bandwidth 250 kHz. We used them to estimate a shape of a source brightness distribution. To measure the angular size of the Sun in a wide frequency band of 8-32 MHz another set of interferometers was used. It consisted of two pairs of the interferometers with the baselines of 225 and 450 m elongated both along the parallel and the meridian. They used digital wideband receivers operating at the frequencies of 8 to 32 MHz to record received signals. There was some sporadic solar activity during observational campaign in March-April 2015 that complicated determination of parameters of the quiet Sun radiation. A large number of radio frequency interference also noted. To mitigate their influence we applied а few data cleaning algorithms. The use of the algorithms in spectral strips with a low level of interferences in periods free from powerful sporadic solar radiation allowed us to make estimation of the angular size of the quiet Sun in two orthogonal directions at some separate frequencies in the range of 20 to 32 MHz. Calculation of the dimensions was performed in an assumption of Gaussian radio brightness distribution of the source. Our estimates of the quiet Sun sizes agree well with the data of other authors. The simplicity and convenience of determining the angular size using the data obtained with two interferometers with different baselines are noted. Continuation such study will allow to extend the frequency range down to the lowest frequencies where observations from the Earth’s surface are possible and give us a possibility to study how the angular size of the quiet Sun depend on a phase of solar activity. This study will allow us to construct a model of solar corona at distances of 1.5-3 solar radii directly from the radio observations and to find out how the effective temperature of the Sun changes with the frequency.